Hansel and Gretel - Southgate, vera (London : Lady bird Ltd)
Once upon a time, in a small village, there lived a poor woodcutter and his two children, Hansel and Gretel. This beloved fairytale takes us on a journey of hardship, courage, and unexpected triumph. Facing abandonment, a treacherous forest, and a wicked witch, Hansel and Gretel demonstrate resilience and resourcefulness. Join me as we explore their remarkable story of survival and the ultimate triumph of good over evil. Hansel and Gretel$1 (Bs world was turned upside down when their mother passed away. Their father, seeking companionship, remarried a woman who turned out to be cruel and heartless. In a desperate act of cruelty, the stepmother led the children deep into the forest and abandoned them. Left alone, Hansel and Gretel relied on their wit and the breadcrumbs Hansel had cleverly dropped along the way. Unfortunately, their breadcrumbs were devoured by hungry birds, leaving the children lost and without a way back home. As they ventured deeper into the forest, hunger and exhaustion began to take hold. But just when all hope seemed lost, a miraculous sight appeared before their weary eyes$1 (Ba cottage made entirely of chocolate, candies, and cake. The siblings, driven by their desperate hunger, couldn$1 (Bt resist indulging in the delectable treats. Unbeknownst to them, the cottage belonged to a wicked witch who lured children into her home with the intention of consuming them. Hansel and Gretel$1 (Bs initial delight quickly turned into a terrifying ordeal as the witch captured them and locked them in a cage. The witch$1 (Bs sinister plan involved making a soup out of Hansel, her first victim. As the pot of water began to boil, Gretel summoned all her courage and devised a daring plan to save herself and her brother.s
Fiction English
Keywords: English - Fiction Book